2022
DOI: 10.1002/adma.202202333
|View full text |Cite
|
Sign up to set email alerts
|

Rhombohedral Pd–Sb Nanoplates with Pd‐Terminated Surface: An Efficient Bifunctional Fuel‐Cell Catalyst

Abstract: Developing high‐performance electrocatalysts for the ethanol oxidation reaction (EOR) and the oxygen reduction reaction (ORR) is essential for the commercialization of direct ethanol fuel cells, but it is still formidably challenging. In this work, a novel Pd–Sb hexagonal nanoplate for boosting both cathodic and anodic fuel cell reactions is prepared. Detailed characterizations reveal that the nanoplates have ordered rhombohedral phase of Pd8Sb3 (denoted as Pd8Sb3 HPs). The Pd8Sb3 HPs exhibit much enhanced act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…Based on the calculated free energy profiles, it is observed that the second dehydrogenation of ethanol (*CH 3 CHOH → *CH 3 COH) was the rate-determining step (RDS) of the C 2 -path of the EOR. 54–56 Notably, PdBi exhibits a lower free energy demand (0.51 eV) in the RDS relative to that of pure Pd (0.88 eV), verifying that the incorporation of Bi atoms can thermodynamically promote the RDS and thus the C 2 pathway in the EOR. This can be attributed to the redistribution of electron charge and the optimized electronic structure of Pd arising from the alloyed Bi.…”
Section: Resultsmentioning
confidence: 85%
“…Based on the calculated free energy profiles, it is observed that the second dehydrogenation of ethanol (*CH 3 CHOH → *CH 3 COH) was the rate-determining step (RDS) of the C 2 -path of the EOR. 54–56 Notably, PdBi exhibits a lower free energy demand (0.51 eV) in the RDS relative to that of pure Pd (0.88 eV), verifying that the incorporation of Bi atoms can thermodynamically promote the RDS and thus the C 2 pathway in the EOR. This can be attributed to the redistribution of electron charge and the optimized electronic structure of Pd arising from the alloyed Bi.…”
Section: Resultsmentioning
confidence: 85%
“…16c shows the CVs of Pd 8 Sb 3 HNP/C, commercial Pd/C, and Pt/C in 0.5 M NaOH containing 0.5 M ethanol with a sweep rate of 50 mV s −1 . 76 A lower onset potential and larger current intensity of Pd 8 Sb 3 HNP/C were observed in comparison with commercial Pd/C and Pt/C, suggesting better anodic electrooxidation activity. Pd 8 Sb 3 HNP/C shows the highest SA of 29.3 mA cm −2 and MA of 4.5 A mg Pd −1 .…”
Section: Electrocatalytic Applications In Fuel Cellsmentioning
confidence: 88%
“…7(a and b). 76 The HAADF-STEM-EDX mappings in Fig. 7b show that the Pd and Sb elements are distributed evenly throughout the whole HNPs.…”
Section: Synthesis Strategiesmentioning
confidence: 91%
“…The OUR of organic compounds in fuel cells seems to be another fascinating strategy for electrosynthesis for both chambers (with oxygen being reduced to hydroxy peroxide) and electricity. Up to now, various alcohols (e.g., ethanol, ethylene glycol, isopropanol, glycerol and Furfural) [ 32 , 34 , 35 , 36 , 37 ] have been demonstrated to have great potential for effectively upgrading fuel cells. Besides fuel cells, upgrading organic compounds can also be realized in other devices, such as zinc–air batteries [ 33 ].…”
Section: Introductionmentioning
confidence: 99%